Effect of radius on various parameters of cylindrical surrounding double-gate (CSDG) MOSFET - E. Oyedeji, Okikioluwa; M. Srivastava, Viranjay (International Journal of Engineering and Technology, 2018)
The MOSFET is an integral component of electronics device and scaling the device is continuously in progress. This research work intro-duces a novel structure of the Cylindrical Surrounding Double-Gate (CSDG) MOSFET to improve scaling and to suppress Short Channel Effect (SCE). In order to achieve this improvement, the drift-diffusion components are used to analyze the drain current of the device through the Pao-Sah integral. Then transconductance is derived to indicate an improved performance of the proposed design. The capaci-tance characteristics of this MOSFET is also analyzed through the equivalent capacitance model as well as the analysis of the carrier mobility, in which it has been observed that scaling of the device supports increase in mobility of the charge carrier.Â Â